Regenerative Medicine of Epithelia: Lessons From the Past and Future Goals - Maurizi, Eleonora; Adamo, Davide; Magrelli, Federica Maria; Galaverni, Giulia; Attico, Eustachio; Merra, Alessia; Maffezzoni, Maria Benedetta Rizzarda; Losi, Lorena; Genna, Vincenzo Giuseppe; Sceberras, Virginia; Pellegrini, Graziella (Frontiers in Bioengineering and Biotechnology, 2021)
This article explores examples of successful and unsuccessful regenerative medicine on human epithelia. To evaluate the applications of the first type of regenerated tissues, an analysis of the past successes and failures addresses some pending issues and lays the groundwork for the new applications. Research should still be encouraged to fill the gap between pathologies, clinical applications and what regenerative medicine can attain with current knowledge.